The Role Of Job Stress Mediation On The Performance Of BSI Financial Institutions - ego pasha, aprielle; Haryono, Slamet (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2024)
Purpose – This study analyzes how work-family conflict and job stress affect BSI Financial Institutions' operational performance. It also uses the work stress model to investigate how a mediating variable affects this performance. Design/methodology/approach – This research used purposive sampling, another name for non-probability sampling, as its sample approach. It relied on a sample of 42 people who were working at BSI Financial Institution. The Sobel test and multiple linear regression analysis are part of the research strategy used in this study. Findings and Discussion – The findings indicate that stress moderates fulfillment and work-family conflict, influencing employee job satisfaction. Furthermore, stress and work-family conflict have a detrimental impact on employees' job satisfaction